Glomalin: characteristics, production, limitations and contribution to soils - Sousa, Carla Silva; Menezes, Rômulo Simões Cezar; Sampaio, Everardo Valadares de Sá Barretto; Lima, Francisco Sousa (Semina: Ciências Agrárias, 2012)
Glomalin is a hydrophobic, heat-stable, and recalcitrant glycoprotein produced by arbuscular mycorrhizal fungi. The glomalin is extracted from the hyphae or from the soil through the use of sodium citrate (20-50 mM; pH 7.0 or 8.0) at high temperature (121 Â°C) and is quantified by ELISA or Bradford methods. Soil characteristics, climatic conditions, land use systems, agricultural practices, presence and type of vegetation, among other factors, influence the amount of glomalin produced by AMF. The 'glue' property of glomalin helps to fixate soil particles, favoring the formation of stable aggregates. Glomalin sequesters heavy metals, reducing the availability and the risk of toxicity of these elements for organisms and plants grown in polluted soils. Depending on the extraction procedure and the origin of the soil, between 28 to 45% dry weight of the glomalin molecule is carbon and 0.9 to 7.3% is nitrogen, representing up to 4 to 5% of total C and N of the soil. Despite the important contribution of glomalin, studies are needed to reformulate the extraction protocol and to identify its physiological function for the AMF, their stocks in different ecosystems, the organisms responsible for its decomposition and consumption, and the AMF species producing more of this protein in the soil.